Predation evidence in the bonaerense coast: Glycymeris longior (Bivalvia) as a possible victim of gastropods - Cristini, Paula Andrea (2022)
Molluscan death assemblages are useful for reconstructing paleocommunities. In spite thatmolluscan predators are rarely preserved in Quaternary marine sediments, they provide signals forevaluating predation recorded as round holes in shells, recognized as the trace fossil Oichnus. Onthe other hand, the bivalve Glycymeris longior is one of the most abundant species found in fossiland modern shell assemblages from the coasts of Buenos Aires Province. Glycymeris longior livesat the surf zone, between the intertidal zone and 20 m depth. Their shells are robust and can resistthe taphonomically active zone, which allows recording the postmortem history of shells. The highabundance of G. longior at Mar del Plata?s coasts suggests that this species could be an importantprey item on the food web. Thus, our study aims to identify Oichnus ichnospecies in G. longiorshells to unveil the possible gastropod predators in modern death assemblages from Mar del Plata.Therefore, we took samples from the high tide line with a quadrat (50 cm x 50 cm) from twobeaches of Mar del Plata. Samples were washed in a 1 mm diameter sieve mesh and 1165 valveswere recovered from Unzué Beach (UB) and 202 valves from Camet Norte Beach (CNB). Shelllengths were measured and Oichnus ichnospecies were identified in G. longior shells. This bivalvecorresponded to 41.8% and 77.7% of the total assemblages in UB and CNB respectively, and therewere no drilling gastropods except the only specimen of the muricean Urosalpinx cala found at UB.However, the 10.7% and 3.2% of G. longior shells from both assemblages exhibited the presence ofdrill holes, specifically Oichnus paraboloides, which possible producers are naticid gastropods.Shell sizes varied between 5.29 mm and 17.19 mm in UB (a sandy beach) and between 19.21 mmand 39.28 mm in CNB (an abrasion platform beach). We expect that smaller shells of G. longior(less robust than larger ones) are more prone to be successfully attacked by gastropods predatorsthan larger ones. In addition, 100% of Oichnus records corresponded to O. paraboloides of smallsizes. Moreover, a higher proportion of these traces were recorded in the sandy bottom assemblage(UB). This might correspond to a predation pressure produced by small-sized naticid gastropods,with low chances to be preserved in the shell assemblage. However, predation pressure is evidenced by drill holes in small shells of G. longior.